The potential impact of moxidectin on onchocerciasis elimination in Africa: an economic evaluation based on the Phase II clinical trial data - Hugo C Turner; Martin Walker; Simon K Attah; Nicholas O Opoku; Kwablah Awadzi; Annette C Kuesel; María-Gloria Basáñez (Parasites & Vectors, 2015)
Abstract Background Spurred by success in several foci, onchocerciasis control policy in Africa has shifted from morbidity control to elimination of infection. Clinical trials have demonstrated that moxidectin is substantially more efficacious than ivermectin in effecting sustained reductions in skin microfilarial load and, therefore, may accelerate progress towards elimination. We compare the potential cost-effectiveness of annual moxidectin with annual and biannual ivermectin treatment. Methods Data from the first clinical study of moxidectin were used to parameterise the onchocerciasis transmission model EPIONCHO to investigate, for different epidemiological and programmatic scenarios in African savannah settings, the number of years and in-country costs necessary to reach the operational thresholds for cessation of treatment, comparing annual and biannual ivermectin with annual moxidectin treatment. Results Annual moxidectin and biannual ivermectin treatment would achieve similar reductions in programme duration relative to annual ivermectin treatment. Unlike biannual ivermectin treatment, annual moxidectin treatment would not incur a considerable increase in programmatic costs and, therefore, would generate sizeable in-country cost savings (assuming the drug is donated). Furthermore, the impact of moxidectin, unlike ivermectin, was not substantively influenced by the timing of treatment relative to seasonal patterns of transmission. Conclusions Moxidectin is a promising new drug for the control and elimination of onchocerciasis. It has high programmatic value particularly when resource limitation prevents a biannual treatment strategy, or optimal timing of treatment relative to peak transmission season is not feasible.